2017
DOI: 10.5194/hess-21-963-2017
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of rainfall events in regional climate model simulations for the Czech Republic

Abstract: Abstract. Characteristics of rainfall events in an ensemble of 23 regional climate model (RCM) simulations are evaluated against observed data in the Czech Republic for the period 1981-2000. Individual rainfall events are identified using the concept of minimum inter-event time (MIT) and only heavy events (15 % of events with the largest event depths) during the warm season (May-September) are considered. Inasmuch as an RCM grid box represents a spatial average, the effects of areal averaging of rainfall data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…In particular, we study the slopes of the 0.05-0.95 quantiles in steps of 0.05 (see Figure 1). This builds upon the results of Moberg et al (2006), who partitioned precipitation distribution in 2%, 5%, 10%, 90%, 95%, and 98% percentiles and calculated the corresponding trends, and Allan and Soden (2008), Rossow et al (2013), Svoboda et al (2016Svoboda et al ( , 2017 who considered discrete 5-10% quantile bins, in a comparison between observed data and model simulations.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we study the slopes of the 0.05-0.95 quantiles in steps of 0.05 (see Figure 1). This builds upon the results of Moberg et al (2006), who partitioned precipitation distribution in 2%, 5%, 10%, 90%, 95%, and 98% percentiles and calculated the corresponding trends, and Allan and Soden (2008), Rossow et al (2013), Svoboda et al (2016Svoboda et al ( , 2017 who considered discrete 5-10% quantile bins, in a comparison between observed data and model simulations.…”
Section: Methodsmentioning
confidence: 99%
“…() and Svoboda et al . () pointed out that the second type of extreme rainfall events may induce more severe flood disasters due to the duration of the rainfall event. The characteristics of rainfall events under the second definition (hereafter rainfall event characteristics) have profound effects on the shape of the resulting hydrograph, soil moisture dynamics and water storage allocation (Jiang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Svoboda et al . () evaluated the ability of 23 regional climate models (RCM) in simulating characteristics of rainfall events such as rainfall depth, rainfall duration and rainfall mean intensity for the period 1981–2000. Most studies have been conducted based on historical data series.…”
Section: Introductionmentioning
confidence: 99%
“…RCMs are also limited in the simulation of convective precipitation events (Maraun et al, 2010b;Svoboda et al, 2016), which is important for the representation of extreme hourly precipitation (Chan et al, 2013). As a consequence, large differences between RCM simulated and observed hourly precipitation extremes are found (Hanel and Buishand, 2010;Gregersen et al, 2013;Chan et al, 2014;Svoboda et al, 2017). In order to overcome the current limitations in terms of RCM precipitation projections, high resolution (1-5 km) RCMs have been tested (Ban et al, 2015;Prein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%